1974
DOI: 10.3758/bf03333428
|View full text |Cite
|
Sign up to set email alerts
|

Cross-modal matching by retarded and normal readers

Abstract: example, have reported that for animals reared in isolation, the presence of other animals had little or no effect upon fear-reduction. On the other hand , for animals reared socially, the presence of other animals resulted in a reduction of fear-conditioned behaviors. This could be the case in the present experiment since all Ss were normally reared in groups. (Received for publication December S, 1973 .) Cross-modal matching by retarded and normal readers* REFERENCES BILLJONEStUniversity of Waterloo, Wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

1980
1980
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…These differences between reading ability groups in short-term memory for sequential patterns are particularly strong and consistent when the sequential patterns are presented auditorially (Badian, 1977;Jones, 1974;Payne, Davenport, Domangue, & Soroka, 1980). Payne et al demonstrated the importance of sequential auditory short-term memory in a study of Birch and Belmont's (1964) hypothesis about the role of intersensory integration in reading ability.…”
mentioning
confidence: 84%
“…These differences between reading ability groups in short-term memory for sequential patterns are particularly strong and consistent when the sequential patterns are presented auditorially (Badian, 1977;Jones, 1974;Payne, Davenport, Domangue, & Soroka, 1980). Payne et al demonstrated the importance of sequential auditory short-term memory in a study of Birch and Belmont's (1964) hypothesis about the role of intersensory integration in reading ability.…”
mentioning
confidence: 84%
“…On fait done l'hypothese qu'il existe d'une part des champs representationnels relativement clos, d'autre part un systerne regulateur qui permet d'ouvrir ou non ces (16) Une telle conception du rOle central du corps dans la vie mentales'inscrit dansdivers courants de la psychologie moderne (notamment, Jones, 1974;Coquery, 1978;Damasio, 1994;Decety ldirl. 2000), lesquels prolongent la perspective philosophique de Bergson (1932).…”
Section: Dynamique Corporelle Et Dynamique Musicaleunclassified